2014
DOI: 10.1063/1.4895932
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency rare-earth emitter for thermophotovoltaic applications

Abstract: In this work, we propose a rare-earth-based ceramic thermal emitter design that can boost thermophotovoltaic (TPV) efficiencies significantly without cold-side filters at a temperature of 1573 K (1300 °C). The proposed emitter enhances a naturally occurring rare earth transition using quality-factor matching, with a quarter-wave stack as a highly reflective back mirror, while suppressing parasitic losses via exponential chirping of a multilayer reflector transmitting only at short wavelengths. This allows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / e n c o n m a n et al shows that ErAG emitters integrated with dielectric mirrors have theoretical TPV conversion efficiency as high as 33% [24]. Magnetic polariton-based emitters were recently proposed to achieve fixed wavelength emission at all angles, which benefits TPV systems using a fixed PV diode bandgap [25].…”
Section: Overview Of Tpv Mechanism and Historymentioning
confidence: 98%
“…e l s e v i e r . c o m / l o c a t e / e n c o n m a n et al shows that ErAG emitters integrated with dielectric mirrors have theoretical TPV conversion efficiency as high as 33% [24]. Magnetic polariton-based emitters were recently proposed to achieve fixed wavelength emission at all angles, which benefits TPV systems using a fixed PV diode bandgap [25].…”
Section: Overview Of Tpv Mechanism and Historymentioning
confidence: 98%
“…Hence, incorporating rare earths into artificial structures could help fine-tune these characteristics, potentially enhancing their spectral efficiency. For example, recent work has shown that improved spectral and TPV system efficiencies for rare-earth-doped garnet emitters with GaSb PV cells can be achieved using the concept of quality factor matching [74]. Additional improvement is expected when the conventional metallic back reflector is replaced by a quarter-wave dielectric stack (QWS), and a chirped dielectric filter on top of the structure is integrated [74], as shown in Figure 7B and 7C.…”
Section: Rare-earth Emittersmentioning
confidence: 99%
“…Although the previously mentioned types of filters were originally designed to be placed at the cold side, which is just above the PV cell or as part of its back reflector [95], an integrated emitter-filter has recently been suggested for improved spectral efficiency of rare-earth emitters [74]. The concept can be applied to any type of selective emitters, including 2D PhCs, after filling their holes with a supportive dielectric for mechanical stability.…”
Section: Filters and Photon Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, these energy losses can be eliminated by selective emitters that have near-blackbody emission above the PV bandgap and low emission below the PV bandgap. 1 Several materials have been proposed for selective emission, including plasmonic metamaterials, 2-4 refractory plasmonic structures, 5 rare earth materials, [6][7][8] and photonic crystals (PhCs). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, realistic selective emitters still have residual low energy emission near the bandgap that can considerably limit the conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%